2021
DOI: 10.1097/lbr.0000000000000756
|View full text |Cite
|
Sign up to set email alerts
|

Lung Navigation Ventilation Protocol to Optimize Biopsy of Peripheral Lung Lesions

Abstract: Background: Computed tomography-to-body divergence caused by respiratory motion, atelectasis, diaphragmatic motion and other factors is an obstacle to peripheral lung biopsies. We examined a conventional ventilation strategy versus a lung navigation ventilation protocol (LNVP) optimized for intraprocedural 3-dimensional image acquisition and bronchoscopic biopsy of peripheral lung nodules.Methods: A retrospective, single center study was conducted in consecutive subjects with peripheral lung lesions measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(84 citation statements)
references
References 23 publications
4
80
0
Order By: Relevance
“…After abstract and full-text review, there were 11 papers (8 original studies and 3 meta-analyses) that specifically evaluated the impact of the anesthesia method on atelectasis, safety, or diagnostic yield during advanced bronchoscopy [4,[27][28][29][30][31][32][33][34][35][36]. Bowling et al compared ENB using general anesthesia versus intravenous sedation and observed diagnostic yields of 70% and 78%, respectively (P = NS) [29].…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…After abstract and full-text review, there were 11 papers (8 original studies and 3 meta-analyses) that specifically evaluated the impact of the anesthesia method on atelectasis, safety, or diagnostic yield during advanced bronchoscopy [4,[27][28][29][30][31][32][33][34][35][36]. Bowling et al compared ENB using general anesthesia versus intravenous sedation and observed diagnostic yields of 70% and 78%, respectively (P = NS) [29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bowling et al compared ENB using general anesthesia versus intravenous sedation and observed diagnostic yields of 70% and 78%, respectively (P = NS) [29]. As will be described in greater detail below, Bhadra et al 2021 observed less atelectasis and a trend toward greater diagnostic yield using an optimized ventilation protocol compared to conventional ventilation [28]. Minami et al (2017) reported that fentanyl and midazolam sedation was useful for peripheral bronchoscopy [32].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations